Correction: Impact of the synthesis method on the solid-state charge transport of radical polymers. Issue 4 (17th January 2018) - Zhang, Yiren; Park, Albert; Cintora, Alicia; McMillan, Stephen R.; Harmon, Nicholas J.; Moehle, Austin; Flatté, Michael E.; Fuchs, Gregory D.; Ober, Christopher K.
Abstract : Correction for 'Impact of the synthesis method on the solid-state charge transport of radical polymers' by Yiren Zhang et al., J. Mater. Chem. C, 2018, 6, 111–118.